Deciphering molecular details in the assembly of alpha-type carboxysome. Issue 1 (December 2018) - Liu, Yilan; He, Xinyuan; Lim, Weiping; Mueller, Joshua; Lawrie, Justin; Kramer, Levi; Guo, Jiantao; Niu, Wei
Abstract Bacterial microcompartments (BMCs) are promising natural protein structures for applications that require the segregation of certain metabolic functions or molecular species in a defined microenvironment. To understand how endogenous cargos are packaged inside the protein shell is key for using BMCs as nano-scale reactors or delivery vesicles. In this report, we studied the encapsulation of RuBisCO into theα -type carboxysome fromHalothiobacillus neapolitan . Our experimental data revealed that the CsoS2 scaffold proteins engage RuBisCO enzyme through an interaction with the small subunit (CbbS). In addition, the N domain of the large subunit (CbbL) of RuBisCO interacts with all shell proteins that can form the hexamers. The binding affinity between the N domain of CbbL and one of the major shell proteins, CsoS1C, is within the submicromolar range. The absence of the N domain also prevented the encapsulation of the rest of the RuBisCO subunits. Our findings complete the picture of how RuBisCOs are encapsulated into theα -type carboxysome and provide insights for future studies and engineering of carboxysome as a protein shell.